1993
DOI: 10.1530/jrf.0.0980617
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive wastage in the androstenedione-immune ewe

Abstract: An experiment was carried out using 320 adult Merino ewes to examine the effects of immunization against an androstenedione human serum albumin conjugate (Fecundin) on ovulation rate, fertilization rate and embryo viability at days 2, 9 and 13-14 after fertilization. The ovulation rate of immunized ewes (2.19 +/- 0.06) was greater (P < 0.001) than that of control ewes (1.43 +/- 0.04). The recovery rate of embryos or of unfertilized oocytes on day 2 was reduced in immunized ewes, but fertilization rate of recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…There was no significant difference in tupping percentage among the treatment groups. Scaramuzzi et al (1993) and Crocker et al (2003) observed no difference in tupping percentage among the treatment groups similar to the present study. Immunization of ewes against androstenedione also had no significant effect on lambing percentage which was in agreement with the findings of Philipon and Driancourt (1987) and Crocker et al (2003).…”
Section: Resultssupporting
confidence: 91%
“…There was no significant difference in tupping percentage among the treatment groups. Scaramuzzi et al (1993) and Crocker et al (2003) observed no difference in tupping percentage among the treatment groups similar to the present study. Immunization of ewes against androstenedione also had no significant effect on lambing percentage which was in agreement with the findings of Philipon and Driancourt (1987) and Crocker et al (2003).…”
Section: Resultssupporting
confidence: 91%
“…Previous studies examining the effects of immunization against androstenedione on conception rate, embryo survival, and lamb performance have been inconsistent but highlight the potential for negative effects of the vaccines on these traits (Boland et al, 1986;Cameron et al, 1988;Croker et al, 1988;Scaramuzzi et al, 1993). Expression of the androgen receptor is widespread in the sheep ovary, but it is unclear if androgens may have a direct effect on the oocyte, as receptors have been noted in oocytes using immunohistochemistry, but no mRNA for androgen receptor could be detected with in situ hybridization (Juengel et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, similar to what was seen with the BMP15 vaccine, the effects of immunization against androstenedione appear primarily limited to alterations in ovulation rate as no differences were observed in conception rate or partial failure of multiple ovulations. Previous studies have shown detrimental effects of immunization against androstenedione on conception rate and early development of the embryo (Boland et al, 1986;Cameron et al, 1988;Scaramuzzi et al, 1993). However, controlling the timing of mating after the booster immunization appears to be a key element in minimizing these detrimental effects as ewes mating 14 d after the booster immunization were more severely affected than those mated 25 d (Boland et al, 1986).…”
Section: Discussionmentioning
confidence: 99%